A Salient Sugar Tax Decreases Sugary-Drink Buying. (November 2021) - Donnelly, Grant E.; Guge, Paige M.; Howell, Ryan T.; John, Leslie K.
Many governments have introduced sugary-drink excise taxes to reduce purchasing and consumption of such drinks; however, they do not typically stipulate how such taxes should be communicated at the point of purchase. Historical, field, and experimental data consisting of more than 225, 000 purchase decisions indicated that introducing a 0.01-per-ounce sugar-sweetened beverage (SSB) tax—without making it salient on price tags—had no significant effect on purchasing (−1.26%, p = .28). However, when the phrase "includes sugary drink tax" was added to tax-inclusive price tags, SSB purchasing was lower than (a) in the pretax period (−9.78%, p < .001), (b) in a posttax period when drinks did not bear price tags (−5.04%, p < .001), and (c) in a posttax period when drinks bore tax-inclusive price tags that did not mention the tax (−3.83%, p = .002). Making the tax's beneficiary (student programs) salient on price tags had no added effect. Two follow-up studies suggested that tax salience was effective partly because consumers overestimated the tax amount, leading to reduced purchase intentions.